Harmonisasi Hukum Tindak Pidana Eksploitasi Seksual Anak Pasca Diratifikasinya Protokol Tambahan Konvensi Hak Anak - Ahmad Sofian; Batara Mulia Hasibuan (Nagari Law Review, 2017)
Sexual exploitation of children is a crime that makes children not only as sex objects as well as commercial objects. This terminology comes from an international criminal law instrument, Commercial Sexual Exploitation of Children (CSEC). In the national context, this terminology has not been mentioned in national criminal law, even academic studies on this issue have not been widely practiced. In addition, the crime of child sexual exploitation has not been regulated in a special article. The terminology found is only about child sexual violence, whose meaning is different from child sexual exploitation. Indonesia has ratified the Optional Protocol on Sale of Children, Child Prostitution and Child Pornography (OPSC), it is important to harmonize national laws related to the crime of child sexual exploitation. This research is normative law research, with approach of legislation. This study found that post-ratification of OPSC through Law no. 10 Year 2012, no steps have been taken to harmonize national criminal law related to child sexual exploitation as required in OPSC, so that measures to improve national law and measures to tackle this criminal problem have not been followed in accordance with the standard desired by OPSC. Therefore, it is recommended that the government immediately take steps to transform the current national law of child protection by incorporating aspects of child sexual exploitation as set forth in the OPSC into the R-Criminal Code and in the revision of the Child Protection Act.